Petrological Study of Ni-Fe Metal in Some Ordinary Chondrites - Nagahara, Hiroko (1979)
P(論文) Mode of occurrence, compositional zoning and bulk chemical composition of metals in the Yamato ordinary chondrites have been studied. Metal grains in the chondrites are discrete taenite and kamacite, and composite grains of the two phases including plessite. They show a remarkable compositional zoning identical to that in iron and stony-iron meteorites. Occasionally Ni-Fe metal coexists with troilite; in such a case, the part in contact with troilite is enriched in Ni. Generally the isopleths of Ni in zoned metal grains are parallel to their outlines, indicating that the compositional zoning was formed in situ. Frequency distribution of bulk chemical composition of metal grains in Yamato-74115 (H5) chondrite shows two distinct peaks at different compositions; one is at the kamacite composition and the other at the taenite composition. Those in Yamato-74354 (L6) and -74190 (L6) chondrites show one distinct peak at the Ni composition intermediate between kamacite and taenite, and two obscured peaks, of which one is at kamacite composition and the other at taenite composition. Based on the Ni-Fe binary phase diagram, it is inferred that metals in H chondrite began to crystallize at least below 700℃ and those in L chondrite below 620℃. Probably kamacite began to crystallize apart from the original taenite grains, but changed its composition in equilibrium with taenite down to 550℃ in H chondrite and 470℃ in L chondrite, having resulted in the formation of the M-shaped zonal pattern. Below this temperature and at least down to 300℃, the two phases were in a partial equilibrium and a remarkable compositional zoning of plessite was formed. departmental bulletin paper